Legal Frameworks and the Efficacy of a Sustainable Livelihood Program for Victims of Mount Merapi Eruption - Triyana, Heribertus Jaka; Prasetiyo, Putri Widhyastiti (Udayana Journal of Law and Culture; Vol 9 No 1 (2025), 2025)
Subsequent to the significant volcanic catastrophe of Mount Merapi eruption in 2010 in Yogyakarta, the Indonesian government, with assistance from non-governmental organizations, commercial organizations, and international benefactors, initiated sustainable livelihood programs for the affected survivors. This study evaluates the effectiveness of a collaborative approach within the sustainable livelihoods program by analyzing key initiatives and interviewing critical stakeholders and communities, focusing on its impact on the resilience of victims' livelihoods following the Mount Merapi eruption in 2010. In this regard, this study aims to cross-examine the legal frameworks, achievements, community actual activities, efforts, and multiplier effects of the livelihood resilience in Cangkringan Subdistrict in order to give feedback in the future as one of the crucial elements of community capacity to mitigate upcoming eruptions as their own culture of adaptation. The social-legal study was conducted through legal analysis of legal instruments on disaster management and primary data collected from the field, such as interviews from farmers, pen breeders, and horticulture respondents, as well as from resource persons such as local authorities and representatives of the Merapi Resilience Consortium and International Organization for Migration, which were involved after the eruption between 2010-2015. Essential components of effective coordination and the allocation of resources among stakeholders and local authorities have proven instrumental in fostering livelihood resilience, despite persistent challenges such as limited access to training, networking opportunities, and essential assets.